Bonus Demografi Sebagai Peluang Pelayanan Misi Gereja di Kalangan Muda-Mudi - Rahmat Kristiono (Sekolah Tinggi Teologi Berita Hidup, 2019)
This paper describes the correlation of bonus demographics with church mission services among young people. The demographic bonus is assumed to be an opportunity for gospel outreach or preaching which has a significant influence on the growth of the church among young people. In the context of the church's mission service, the demographic bonus has not been optimally optimized by the church, especially to place millennials on the mission objectives of the church. AbstrakTulisan ini mendeskripsikan korelasi bonus demograﬁ dengan pelayanan misi gereja di kalangan muda-mudi. Bonus demograﬁ diasumsikan sebagai peluang penjangkuan atau pemberitaan injil yang membawa pengaruh signifikan bagi pertumbuhan gereja dikalangan muda-mudi. Dalam konteks pelayanan misi gereja, Bonus demograﬁ belum dioptimalkan secara maksimal oleh gereja terutama menempatkan kaum milenial pada sasaran misi gereja.